2020
DOI: 10.1016/j.gore.2020.100659
|View full text |Cite
|
Sign up to set email alerts
|

Undergoing active treatment for gynecologic cancer during COVID-19: A qualitative study of the impact on healthcare and social support

Abstract: Highlights COVID-19 challenges mechanisms of gynecologic cancer care delivery. COVID-19 complicates social support for cancer patients undergoing active treatment. Patient narratives of COVID-19 may offer targeted solutions to improve care delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 17 publications
(11 reference statements)
2
31
0
2
Order By: Relevance
“…In the present study, increased care with hygiene, decreased visits, spending more time with family at home and social isolation and other preventive measures during the pandemic were found to have a positive effect on the women receiving treatment for cancer. Likewise, in a qualitative study by Moran et al one participant reported that she felt lucky since her illness coincided with the pandemic ( Moran et al, 2020 ). The participant explained that she did not miss anything and had the comfort of working from home since everybody was exposed to the same restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, increased care with hygiene, decreased visits, spending more time with family at home and social isolation and other preventive measures during the pandemic were found to have a positive effect on the women receiving treatment for cancer. Likewise, in a qualitative study by Moran et al one participant reported that she felt lucky since her illness coincided with the pandemic ( Moran et al, 2020 ). The participant explained that she did not miss anything and had the comfort of working from home since everybody was exposed to the same restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients have been reported to put emphasis on religious sources to cope with existential worries resulting from the pandemic ( Peteet, 2020 ). Moran et al found in their qualitative study that patients with gynecological cancers developed creative coping strategies like visiting the church online, going for a walk instead of going to the gym and meeting friends by keeping the physical distance ( Moran et al, 2020 ). In the study of Hintermayer et al cancer patients were found to use similar strategies such as acknowledging the importance of the family and the society, developing personal coping strategies, feeling relieved thanks to their religious beliefs and talking about the things felt grateful for ( Hintermayer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Across all oncologic subspecialties, patients who require ongoing cancer treatment have expressed concern about disease progression based on altered treatment plans due to the pandemic. 15 18 Although newer studies, including those in early-stage breast and prostate cancers, provide data to suggest that treatment delays will not be associated with worse outcomes, 19 , 20 the consequences of surgical delays will not be fully understood for years to come. However, the distress due to cancer and COVID is already present, and screening and treatment should occur in real time.…”
Section: Discussionmentioning
confidence: 99%
“…While programs exist nationally to connect gynecologic cancer patients from all over the country [ 14 , 15 ], our participants noted the importance of connecting with someone regionally, and the shift to virtual communication may also facilitate this in a rural state. Finally, healthcare systems should take advantage of the now robust electronic medical record system to deliver “support bundles” to their patients, containing links to resources and support groups [ 16 ]. Recruitment to the W2W program may be offered as part of the intake process to every newly diagnosed gynecologic cancer patient.…”
Section: Discussionmentioning
confidence: 99%